If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=10+2x
We move all terms to the left:
-12-(10+2x)=0
We add all the numbers together, and all the variables
-(2x+10)-12=0
We get rid of parentheses
-2x-10-12=0
We add all the numbers together, and all the variables
-2x-22=0
We move all terms containing x to the left, all other terms to the right
-2x=22
x=22/-2
x=-11
| (2x+3)^2=48 | | 6c−8−2c=−16. | | 1-5x-8=1-6x | | -4(-7x+4)-4x=1 | | 7=v/2+5 | | 7x/2x^2-15=-1 | | -2-(x+3)=-7 | | 2/15w=1+1/9w | | 3(2x+6)=2(4x5) | | 6d−11/2=2d-13/2 | | 2v–5v=15 | | 119=-x+189 | | (5y+6)^2=48 | | 4x^2-29x+6=0 | | 1/3(7-7x)=-21 | | 8x5=2 | | 3=-s–83 | | -9+n-2+6n=5n+3 | | 7x/2x^2-5=-1 | | 50+15w=500 | | -x-13+3x-15=-6 | | z=12.1=14 | | -2=-u+16 | | 1-2x=x-21 | | 22+26x=29+25x | | 60=-4m | | (x+3)2=x2+2x−3 | | 9=t/2+7 | | 9(12+q)=9 | | -9+n-2+6n=5n | | 7m+9/7=14 | | 5+2(-4x-1)=5x-3(4x-5) |